Bile Acids Gate Dopamine Transporter Mediated Currents - Romanazzi, Tiziana; Zanella, Daniele; Cheng, Mary Hongying; Smith, Behrgen; Carter, Angela M.; Galli, Aurelio; Bahar, Ivet; Bossi, Elena (Frontiers in Chemistry, 2021)
Bile acids (BAs) are molecules derived from cholesterol that are involved in dietary fat absorption. New evidence supports an additional role for BAs as regulators of brain function. Sterols such as cholesterol interact with monoamine transporters, including the dopamine (DA) transporter (DAT) which plays a key role in DA neurotransmission and reward. This study explores the interactions of the BA, obeticholic acid (OCA), with DAT and characterizes the regulation of DAT activity via both electrophysiology and molecular modeling. We expressed murine DAT (mDAT) in Xenopus laevis oocytes and confirmed its functionality. Next, we showed that OCA promotes a DAT-mediated inward current that is Na+-dependent and not regulated by intracellular calcium. The current induced by OCA was transient in nature, returning to baseline in the continued presence of the BA. OCA also transiently blocked the DAT-mediated Li+-leak current, a feature that parallels DA action and indicates direct binding to the transporter in the absence of Na+. Interestingly, OCA did not alter DA affinity nor the ability of DA to promote a DAT-mediated inward current, suggesting that the interaction of OCA with the transporter is non-competitive, regarding DA. Docking simulations performed for investigating the molecular mechanism of OCA action on DAT activity revealed two potential binding sites. First, in the absence of DA, OCA binds DAT through interactions with D421, a residue normally involved in coordinating the binding of the Na+ ion to the Na2 binding site (Borre et al., J. Biol. Chem., 2014, 289, 25764–25773; Cheng and Bahar, Structure, 2015, 23, 2171–2181). Furthermore, we uncover a separate binding site for OCA on DAT, of equal potential functional impact, that is coordinated by the DAT residues R445 and D436. Binding to that site may stabilize the inward-facing (IF) open state by preventing the re-formation of the IF-gating salt bridges, R60-D436 and R445-E428, that are required for DA transport. This study suggests that BAs may represent novel pharmacological tools to regulate DAT function, and possibly, associated behaviors.